Mistaken Identity : The Supreme Court and the Politics of Minority Representation - Bybee, Keith J., 1965- (Book collections on Project MUSE., 1998)
Is it ever legitimate to redraw electoral districts on the basis of race? In its long struggle with this question, the U.S. Supreme Court has treated race-conscious redistricting either as a requirement of political fairness or as an exercise in corrosive racial quotas. Cutting through these contradictory positions, Keith Bybee examines the theoretical foundations of the Court's decisions and the ideological controversy those decisions have engendered. He uncovers erroneous assumptions about political identity on both sides of the debate and formulates new terms on which minority representati.